Hubungan antara pengetahuan dan konsumsi makanan dan minuman instan dengan status izi remaja putri - Badraningsih Lastariwati, Nani Ratnaningsih (Berita Kedokteran Masyarakat (BKM), 2006)
Background: Development of science and technology in food industry results in new products such as instant foods. Instant foods are food and drink which have been cooked or semi cooked and then processed to be ready to eat. Consumption of instant foods can affect nutrition status especially in adolescents. Consumption behavior of instant food have been affected by intrinsic factors such as age, sex, and religion, and extrinsic factors such as knowledge, economic level, experiences, advertisement, home environment, and social culture. Objective: The objective of research is to study relationship between knowledge level and consumption of instant food and drink with nutrition status of female adolescents. Methods: Research sample is fifty female adolescents in rooming house at Sagan Village, Caturtunggal, Depok, Sleman, Yogyakarta. Research instruments are closed questionnaire about knowledge of instan foods: seven day food recall and food consumption on consumption frequencies of instan foods; and measurement of nutrition status with anthropometry guided by NCI-IS. Knowledge of respondent is scored 1 (if right) and 0 (if wrong). Consumption frequencies of instant food are scored by Suhardjo method. Correlation product moment is used to analyze relationship between knowledge level and consumption of instant food and nutrition status of respondent. Data are descriptively analyzed. Results and conclusion: Knowledge levels on instant food of female adolescents were categorized: 22% high, 50 % intermediate, and 28% low. Mie instant and coffee instant are most consumed compared with other instant foods. Nutrition status of female adolescent was categorized 74% normal, 22% under weight, 4% over weight, and none categorized obese. Knowledge level and consumption of instant food have positive and significant relationship with nutrition status of female adolescent. Some factors that affect female adolescents on consumption of instant food are knowledge level, economic level, consumption reason, and information of instant food. Keywords: instant food, nutrition status, female adolescents